Effects of active and passive conservation on forest structure and bird diversity in Färna Ecopark - Sandström, Arvid (2021)
Voluntary set-asides are an important part of the conservation of forest species in Sweden. Set aside stands are either treated passively by leaving them untouched (in Swedish abbreviated as NO) or with active, often invasive maintenance (NS). Färna Ecopark is an area with 2 822 hectares productive forest, since 2005 dedicated to conservation of biodiversity and contain both NO and NS forest stands. The forest has a distinctly high proportion of deciduous trees for the region and most stands being subject to conservation are treated to maintain this distinction. My study aims to examine what effect the two different modes of conservation treatment has had on forest structure and their local assemblage of forest birds. The forest structure in eleven NO stands and ten NS stands was measured and compared to each other as well as with ten coniferous production stands in the same area and of a similar age. Bird survey data from the same stands were also examined and compared. I found that the NO stands were more structurally diverse, had a greater proportion of deciduous trees and had local bird assemblages richer in species when compared to the production stands. I could also demonstrate a correlation between forest structural diversity and bird species richness across all treatment groups. The studied NS stands showed great variation between stands in several aspects of forest structure and bird assemblage composition. There were also more bird species observed exclusively in the NS stands compared to the other treatment groups. Likely, this variation is a result of the greater variation in the form of treatment that different NS stands have received. It also made the NS stands hard to study as a group and no statistically significant differences were found between them when compared to the other groups of stands in the study. Therefore, I have concluded that to make inferences concerning the effects of active conservation maintenance, a greater sample of stands is required, and they should be subdivided by the way stands have been maintained.